ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B11110063, Nota Kulata Lasti (Jurnal Manajemen Update, 2015)
The stock price is the price of a stock is determined at the time the stock market is underway with based on the supply and demand on the stock in question. Share prices of the food industry is inseparable from the factors that influenced them such as total assets, total debt, capital, number of sales or net profits earned. Each year between the years 2008-2011 stock price each company's food and beverage industry experience fluctuations. The magnitude of the stock prices also have different values for each company. The purpose of this research is to know the influence of factors in financial ratios i.e. ratio of profitability, liquidity ratios, leverage ratio and the ratio of activity against share price. This research is expected to benefit investors in taking investment decisions and as a judgment upon the achievements and performance of the company. The regression model used was multiple linear regression. Test results simultaneously generates the value F of 63,916 count greater than F table 2,540. This indicates that the variables are independent EPS, ROA, ROE, and the WCT had simultaneous influence against share price. Adjusted R2 value of 0,810 meaning of 81% share price variability can be explained by the independent variable while the remaining 19% is explained by other factors not examined. Partial test results also shows only variables that have an impact on EPS stock price as it has the value significance of 8,815 greater than t count of 2,004 From this research it can be seen that the EPS referable to see financial performance of food and beverage industry during 2008-2011. so that the EPS is the most influential factor for the assessment of the stock price. Keywords: stock price, EPS, financial performance, financial ratios.